Awareness on cancer cervix, willingness, and barriers for screening of cancer cervix among women: A community-based cross-sectional study from urban Pondicherry - K Chandrika; Bijaya Nanda Naik; Srikanta Kanungo (Wolters Kluwer Medknow Publications, 2020)
Background: Early detection of cervical cancer can significantly reduce the associated morbidities and mortality. However, uptake of screening for cervical cancer in India is not encouraging. Objectives: To assess the awareness about cervical cancer, willingness, and barriers for undergoing screening of cervical cancer among women in urban Pondicherry. Methods: This cross-sectional study was conducted among women of 30-65 years in urban Pondicherry during January - July 2019. A total of 219 women, selected using two-stage random sampling, were interviewed using a pretested semi-structured questionnaire. Multistep multivariable logistic regression was done to identify the independent correlates of willingness to undergo screening for cervical cancers. Results: About one-third women were aware of cervical cancer. Awareness was more among women who were young, had higher education, had family history of cancer, and currently working. Awareness of risk factors, signs and symptoms of cancer cervix was low. Although 60% of the women, who have been aware of cervical cancer, were aware of possibility of early detection, <15% were aware of the various methods. 32% of the women were willing to undergo screening for cervical cancer, and occupation, family history of cancer, and knowledge about risk factors were found to be independent correlates. Fear and "not having signs and symptoms" were the major reasons for unwillingness. Conclusion: Level of awareness and willingness for undergoing screening of cervical cancer was low in study area. Targeted interventions for awareness and health system efforts for addressing the reasons behind unwillingness are required.